TIJORAT BANKLARIDA XALQARO PUL O‘TKAZMALARI, ULARNING HISOBI VA AUDITINI TAKOMILLASHTIRISH - Bobomurodov Shamshod Erkin o'g'li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article covers the issues of improving international money transfers, their accounting and audit in commercial banks in Uzbekistan. The study analyzed innovative solutions used by banks on international money transfers. Proposals and recommendations have also been developed aimed at improving the process of international money transfer accounting and auditing.